2020
DOI: 10.1186/s12992-020-00648-2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-border COVID-19 spread amidst malaria re-emergence in Venezuela: a human rights analysis

Abstract: Background Since 2016 Venezuela has seen a collapse in its economy and public health infrastructure resulting in a humanitarian crisis and massive outward migration. With the emergence of the novel coronavirus SARS-CoV-2 at the end of 2019, the public health emergency within its borders and in neighboring countries has become more severe and as increasing numbers of Venezuelans migrants return home or get stuck along migratory routes, new risks are emerging in the region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…For example, some malaria prevention interventions like ITN distribution and malaria-related training were halted because of discouraging gatherings. The observed pattern has been reported elsewhere [ 62 , 63 ]. Educational gatherings are helpful in supporting behaviors to prevent and control malaria.…”
Section: Discussionsupporting
confidence: 88%
“…For example, some malaria prevention interventions like ITN distribution and malaria-related training were halted because of discouraging gatherings. The observed pattern has been reported elsewhere [ 62 , 63 ]. Educational gatherings are helpful in supporting behaviors to prevent and control malaria.…”
Section: Discussionsupporting
confidence: 88%
“…Movement of infectious diseases such as malaria and COVID-19 across borders poses a major obstacle to achieving and maintaining elimination [1,9,10]. The ndings in our study have revealed that 6 asymptomatic infections detected, accounting for 5.6% of all migrant population from Vietnam.…”
Section: Discussionmentioning
confidence: 66%
“…As the pandemic continued, new light was shed on the effect of LAC migrant crises on public health and vaccination policies [ 136 ]. Venezuela was deeply impacted [ 137 , 138 ]. By August 2022, more than 6.8 million Venezuelans fled the country due to political, social, and economic turmoil in what is now considered the largest international displacement in LAC in contemporary history [ 136 ].…”
Section: Discussionmentioning
confidence: 99%